2001
DOI: 10.1002/jpp.343
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy against achromic M6 melanocytes: phototoxicity of lipophilic axially substituted aluminum phthalocyanines and hexadecahalogenated zinc phthalocyanines

Abstract: Lipophilic and axially substituted tri-n-hexylsiloxy aluminum phthalocyanine and cholesteryloxy diphenylsiloxy aluminum phthalocyanine were synthesized and assayed in PDT against M6 melanocytes. In the conditions used ( > 480 nm, 10 mW cm À2 , egg-yolk lecithin or cremophor EL formulation) they both exhibited a higher photodynamic effect than chloroaluminum phthalocyanine. They displayed 2% to 3.5% cell viability at 10 À5 M dose for 20 min irradiation. Hexadecafluoro zinc phthalocyanine was synthesized to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
2
12
1
Order By: Relevance
“…The comparison of the IC 50 values, obtained from dose-response curves, revealed that 4 showed a higher potency than 5 ( Table 2). This is consistent with the conclusion that lipophilic photosensitizers are preferentially transported by lipoproteins, which are uptaken directly by tumor cells and favoring the cell killing efficacy in comparison with the hydrophilic one, as reported by Jori and co-workers [30][31][32].…”
Section: Photocytotoxicity Studiessupporting
confidence: 92%
“…The comparison of the IC 50 values, obtained from dose-response curves, revealed that 4 showed a higher potency than 5 ( Table 2). This is consistent with the conclusion that lipophilic photosensitizers are preferentially transported by lipoproteins, which are uptaken directly by tumor cells and favoring the cell killing efficacy in comparison with the hydrophilic one, as reported by Jori and co-workers [30][31][32].…”
Section: Photocytotoxicity Studiessupporting
confidence: 92%
“…Decreau et al . [ 106 ] reported increasing phototoxicity with increasing the hydrophobicity of AlClPc derivatives. Indeed, when incorporated into liposomal (Egg Yolk Lecithin based liposomes) or emulsion (Cremophor EL based emulsion) formulations, the hydrophobic aluminium Pc (AlPc) derivatives such as 7 and its cholesterol derivative 8 ( Figure 5 ) were more phototoxic than 6 .…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…Around 80 000 tons per year of phthalocyanines are produced to be used as dyes and pigments (Wö rhle, 2001). They are excellent pigments with good thermal and chemical stabilities and they have found wide applications in different fields, including liquid crystals, chemical sensors, photodynamic cancer therapy (Decreau et al, 2001), non-linear optics, molecular electronics, gas sensors, photosensitisers, catalysts, semiconductive materials, photovoltaic cells and electrochromic displays (McKeown, 1998;Leznoff & Lever, 1989-1996.…”
Section: Commentmentioning
confidence: 99%